2013
DOI: 10.1007/8904_2013_264
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular and Saccadic Abnormalities in Gaucher’s Disease

Abstract: Gaucher's disease (GD) is a hereditary lysosomal storage disease characterized by abnormal deposition of glucocerebroside due to the enzyme glucocerebrosidase deficiency, resulting in multi-organ pathology. GD type III has a progressive neurological involvement. We studied the vestibular and saccadic abnormalities in GD type III to determine if these parameters may be useful for assessing neurological involvement. We evaluated the vestibular and saccadic responses of two siblings with genetically identified GD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…As horizontal and later vertical saccades are highly impaired early in the course of the disease, they were used as a primary endpoint to investigate treatment with miglustat ( 5 ). A study of two siblings with GD3 suggested that the vestibulo-ocular reflex (VOR) might also be impaired in GD3 patients ( 6 ). Although saccadic eye movement abnormalities have been described, a comprehensive study of all forms of eye movements in GD3, including pursuit and vestibular-related movements in a large cohort of GD3 patients, has not been published yet.…”
Section: Introductionmentioning
confidence: 99%
“…As horizontal and later vertical saccades are highly impaired early in the course of the disease, they were used as a primary endpoint to investigate treatment with miglustat ( 5 ). A study of two siblings with GD3 suggested that the vestibulo-ocular reflex (VOR) might also be impaired in GD3 patients ( 6 ). Although saccadic eye movement abnormalities have been described, a comprehensive study of all forms of eye movements in GD3, including pursuit and vestibular-related movements in a large cohort of GD3 patients, has not been published yet.…”
Section: Introductionmentioning
confidence: 99%
“…44 Otherwise, BVD may be observed in spinocerebellar ataxia (SCA) types 1, 2, 3, and 6, episodic ataxia type 2, Friedreich's ataxia, Gaucher's disease, and Cronkhite-Canada's syndrome. 3,4,[45][46][47][48][49] Of note, bilateral deafness is usually associated with BVD in Friedreich's ataxia. 50 In patients with advanced SCA type 6, a pure cerebellar form of SCA, the bilaterally positive HITs are probably because of the floccular involvement.…”
Section: Neurodegenerative and Hereditary Disordersmentioning
confidence: 99%
“…85 Global loss of SCC function can cause confusion with BV, but the paucity or slowing of catch-up saccades provides the diagnostic clue. 86 Vestibular deficits in Gaucher's disease likely reflects neuronal loss in the abducens and vestibular nuclei. 87 Eye movement and vHIT abnormalities have been shown to correlate with clinical rating scales, representing promising biomarkers for future clinical trials.…”
Section: Metabolic Disordersmentioning
confidence: 99%